Colonisation of South African kelp-bed canopies by the alien mussel Mytilus galloprovincialis: extent and implications of a novel bioinvasion. Issue 2 (2nd April 2020) - Lindberg, C; Griffiths, CL; Anderson, RJ
Abstract : The Mediterranean mussel Mytilus galloprovincialis is the most significant invasive alien marine species in South Africa and, although not normally found subtidally, has recently been observed colonising heads and stipes of the kelp species Ecklonia maxima in False Bay. We quantified this invasion and explored its ecological implications. Transects laid across kelp beds revealed that 10.34% of kelp individuals surveyed bore canopy mussels, with kelp heads (10.07%) being far more commonly infected than stipes (0.27%). Twenty kelp individuals with infected heads and 20 with infected stipes were separately collected for more-detailed examination. Wet mass of mussels on these kelp heads ranged from 2.5 to 2 462 g (median 86.4 g, interquartile range 14.8–353.8 g) and that of mussels on the stipes from 7.6 to 3 492 g (median 595.5 g, interquartile range 194.0–955.0 g). Mussel clumps consisted mostly of individuals <40 mm in length. Mussel clumps supported a rich biota of 80 invertebrate and 13 algal species. Larger clumps supported more epibiotic species, and those on stipes more species than those of comparable mass on kelp heads. The mussels and their associated epibiotic species negatively affected kelp buoyancy, but rarely enough to overcome natural buoyancy. Some kelp individuals that had been toppled by the weight of mussels and their epibiotic species, however, were encountered in situ . Implications of this invasion include large increases in animal biomass and species richness in the kelp canopy, plus reductions in kelp buoyancy and increased hydrodynamic drag on infected kelps, increasing their probability of being uprooted. Uprooted kelp individuals can raft long distances, potentially transporting both native and alien species to distant sites.